Encouraging Sustainable Development through ZIS: The Role of Islamic Philanthropy in Reducing Poverty and Enhancing Socioeconomic Welfare - Nur Aisyah Indarningsih; Suci Wulandari Siregar; Hasbi Hasbi; Zahra Ramadhani Jasman (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
In an effort to achieve sustainable development, Islamic philanthropy through Zakat, Infaq, and Sadaqah (ZIS) plays an important role in reducing poverty and improving socio-economic welfare. This study aims to analyze the role of Zakat, Infaq, and Sadaqah (ZIS) as an instrument of Islamic philanthropy on poverty, income inequality, human development index and purchasing power in Indonesia in the long and short term. The data analysis techniques used in this study are in the form of Two-Way Fixed Effect Models-GMM for short-term testing and Vector Error Correction Model (VECM) for long-term. The results show that ZIS has a significant negative influence on poverty, income inequality, and HDI, both in the short and long term, indicating that ZIS distribution can help reduce social inequality and improve people's quality of life. In addition, ZIS has been shown to have a positive impact on people's purchasing power, which shows that the assistance provided can increase the economic capacity of individuals. This study suggests that governments and Islamic philanthropic institutions, such as BAZNAS, strengthen the management and distribution of ZIS with a focus on economic empowerment to maximize its impact on sustainable development.